Transport and Point Contact Measurements on Pr1−xCexPt4Ge12 Superconducting Polycrystals - Paola Romano; Francesco Avitabile; Angela Nigro; Gaia Grimaldi; Antonio Leo; Lei Shu; Jian Zhang; Antonio Di Bartolomeo; Filippo Giubileo (Nanomaterials, 2020)
We performed a detailed investigation of the superconducting properties of polycrystalline Pr1−xCexPt4Ge12 pellets. We report the effect of Ce substitution, for x = 0.07, on magnetic field phase diagram H-T. We demonstrate that the upper critical field is well described by the Ginzburg–Landau model and that the irreversibility field line has a scaling behaviour similar to cuprates. We also show that for magnetic fields lower than 0.4 T, the activation energy follows a power law of the type ?−1/2, suggesting a collective pinning regime with a quasi-2D character for the Ce-doped compound with x = 0.07. Furthermore, by means of a point contact Andreev reflection spectroscopy setup, we formed metal/superconductor nano-junctions as small as tens of nanometers on the PrPt4Ge12 parent compound (x = 0). Experimental results showed a wide variety of conductance features appearing in the dI/dV vs. V spectra, all explained in terms of a modified Blonder–Tinkham–Klapwijk model considering a superconducting order parameter with nodal directions as well as sign change in the momentum space for the sample with x = 0. The numerical simulations of the conductance spectra also demonstrate that s-wave pairing and anisotropic s-waves are unsuitable for reproducing experimental data obtained at low temperature on the un-doped compound. Interestingly, we show that the polycrystalline nature of the superconducting PrPt4Ge12 sample can favour the formation of an inter-grain Josephson junction in series with the point contact junction in this kind of experiments.